1992
DOI: 10.1152/jappl.1992.72.4.1235
|View full text |Cite
|
Sign up to set email alerts
|

Air embolism-induced lung injury in isolated rat lungs

Abstract: Pulmonary air embolism causes physical obstruction of microvasculature and leads to permeability changes, release of mediators, and injury to lung tissue. In this study we employed an isolated perfused rat lung model to investigate the primary and secondary effects produced by infusion of air into the pulmonary artery. Infusion of various doses of air (0.10-0.25 ml) over a 1-min period produced a dose-dependent increase in pulmonary arterial pressure and lung weight gain. In contrast, when a constant air dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 0 publications
6
68
0
2
Order By: Relevance
“…Changes in body weight (BW) were considered to be the result of changes in lung weight (LW). Our earlier examinations of isolated lung preparations in which Evans blue dye was added to the perfusate revealed that the dye was confined to the lungs after exposure to either low (2.5 mm Hg) or high (10 mm Hg) PVP for 30 min [18,22]. Although the hematocrit was reduced in the perfusate, the perfusate osmolarity (285 mosm) was not significantly altered compared to that of whole blood.…”
Section: Isolation and Perfusion Of Rat Lungsmentioning
confidence: 97%
See 1 more Smart Citation
“…Changes in body weight (BW) were considered to be the result of changes in lung weight (LW). Our earlier examinations of isolated lung preparations in which Evans blue dye was added to the perfusate revealed that the dye was confined to the lungs after exposure to either low (2.5 mm Hg) or high (10 mm Hg) PVP for 30 min [18,22]. Although the hematocrit was reduced in the perfusate, the perfusate osmolarity (285 mosm) was not significantly altered compared to that of whole blood.…”
Section: Isolation and Perfusion Of Rat Lungsmentioning
confidence: 97%
“…The procedure used to prepare isolated, perfused lungs was similar to that described previously [6,18,22]. Rats were tracheotomized under pentobarbital anesthesia (30 mg/kg i.p.…”
Section: Isolation and Perfusion Of Rat Lungsmentioning
confidence: 99%
“…Thus, the decreased diameter may indicate that the vessels were in a partially constricted state. Vasoconstrictors such as thromboxane A2 (Fukushima & Kobayashi, 1986) and endothelin-1 (Wang et al, 1992) are released during air embolization and their effects may be maintained after the vessels are removed from the lung.…”
Section: Passive Vessel Propertiesmentioning
confidence: 99%
“…LUNG DISEASES, SUCH AS ASTHMA (10), chronic obstructive pulmonary disease (12), endotoxin shock (33), and vascular microembolism (50), or inhalation of oxidant irritants, such as toxic smoke (35), cigarette smoke (35), and ozone (45), may cause increased pulmonary production of reactive oxygen species from endogenous and/or exogenous sources. The major reactive oxygen species are the superoxide anion radical, hydrogen peroxide (H 2 O 2 ), and the hydroxyl radical (⅐ OH) (5).…”
mentioning
confidence: 99%